Anaesthesia for renal transplantation. Issue 8 (August 2021) - Meredith, Sarah; Basavaraju, Aravind; Logan, Neil
Abstract: Renal transplantation is the most common solid organ transplant performed and it is the treatment of choice for end-stage renal disease (ESRD). These patients present a unique set of challenges to the anaesthetist, who has a crucial role in the immediate success of the transplanted organ. This article describes the assessment of the adult patient for renal transplantation, the perioperative management and the aims in the postoperative period.